Pupillary capture following sutureless scleral-fixated intraocular lens in children with Marfan syndrome - Dong-Mei Qi; Shu-Jia Huo; Tao Yu (International Journal of Ophthalmology, 2023)
AIM: To compare the clinical outcomes between two approaches for sutureless scleral-fixated intraocular lens (SFIOL) in children with Marfan syndrome (MFS). METHODS: The study included 15 children (26 eyes) with lens subluxation due to MFS. These children underwent lensectomy, anterior vitrectomy, and sutureless SFIOL. According to the position of placement of intraocular lens (IOL) haptics, two study groups were reviewed for best corrected visual acuity (BCVA) and postoperative complications: group A, 14 eyes with haptics fixated at 2.0 mm from the limbus; group B, 12 eyes with the haptics fixated at 2.5 mm from the limbus. RESULTS: The mean axial length for all patients was 25.66±2.35 mm. Postoperative BCVA in logMAR were significant improved in both groups (0.77±0.32 to 0.17±0.12 in group A, 0.66±0.25 to 0.24±0.12 in group B, both P<0.001) while no significant difference between two groups (P>0.05). Pupillary capture was main postoperative complication, occurring between 3d and 18mo. It occurred in 7 eyes in group A and one eye in group B (P=0.02). CONCLUSION: Sutureless SFIOL is an effective treatment approach for lens subluxation in children with MFS. Pupillary capture is the main postoperative complication. Fixated IOL haptics at 2.5 mm from the limbus can reduce the occurrence of pupillary capture.